Trends in Pre-Trial Detention Practices in Lithuania: Perspectives of Legal Culture - Bikelis, Skirmantas (Kriminologijos studijos, 2018)
[full article and abstract in Lithuanian; abstract in English] This article presents some of the results from the research project “DETOUR: Towards Pre-Trial Detention as Ultima Ratio,” funded by the European Commission (2016– 2017), where the author of the article, together with his colleague V. Pajaujis from the Law Institute of Lithuania, as well as project partners from Austria, Germany, Ireland, Belgium, the Netherlands and Romania, addressed the legal, procedural-structural and legal-cultural particularities in different countries that might be the roots of the different practices in pre-trial investigation when deciding on coercive measures for suspects. The research was particularly focused on the views and attitudes of the practitioners: judges, prosecutors, defense lawyers. Multiple semistructural interviews (no less than 35 per project partner), and four international events with the practitioners’ participation, have been carried out during the project. First, the article presents and discusses the dynamics of statistics in pre-trial detention in Lithuania. Some factors that make impact on statistics that have no relation to the changes of the legal culture in pre-trial investigations are discussed. However, the author comes to the conclusion that even revised statistics indeed indicate a huge drop in the prevalence of pre-trial detention. This assumption is further confirmed by the opinions of the respondents and by the particular instances of objective and subjective factors that might have impact on the downward trend in the application of pre-trial detention. Among the objective factors, the positive experiences of the practitioners in the effective operation of the European arrest warrant have been noted. Also, the practice of the European Court of Human Rights, which emphasized the importance of the equality of parties and the adversarial principle in detention hearings, highly contributed to the elimination of ill-practices, whereas before and during the detention hearings prosecutors used to provide less information from files for the defense than for the judge. The interviews with prosecutors and judges showed instances of a positive shift in attitudes from an orientation toward (or even an over-emphasis of) securing the proceedings to a reasonable balance between the interests of justice and the protection of human rights. It seems that this shift is closely connected with higher standards motivating pre-trial detention. Also, standards of professional contacts between the police and the prosecution, and between the prosecution and the judiciary, have reportedly risen quite substantially, especially in bigger cities. Even though the Lithuanian justice system still employs more coercion in the pre-trial investigation (more detention) against suspects more than most of the European countries, the general outlook in this field is rather optimistic.